Application of Moist Wound Healing Technique in Post-Cesarean Section Patients: A Case Study - Nur Israwati; Amir, Haeril; Mappanganro, Andi (An Idea Nursing Journal, 2025)
Cesarean section is a surgical procedure involving an incision through the abdominal wall and uterus to deliver the baby. Although it is widely performed to ensure the safety of both mother and infant, this procedure often results in wounds that require specific care for optimal healing. This study aimed to explore the application of the Moist Wound Healing (MWH) technique in post- cesarean section wound management. A case study design was employed, focusing on a patient (Mrs.D) who underwent post-cesarean wound care using the MWH technique at Griya Afiat Gowa independent practice clinic. Following diagnosis, the planned nursing intervention involved wound care using theMWH approach. After three sessions of wound care, notable improvements were observed: during the first and second visits, the wound exhibited >25% serous exudate, 80% granulation tissue, and 20% slough. By the third visit, the wound showed 80% granulation, a reduction of slough to 15%, and the presence of 5% epithelial tissue. These findings indicate that the Moist Wound Healing technique is effective in promoting wound healing following cesarean section.